2014
DOI: 10.1002/ajmg.c.31414
|View full text |Cite
|
Sign up to set email alerts
|

The ARID1B phenotype: What we have learned so far

Abstract: Evidence is now accumulating from a number of sequencing studies that ARID1B not only appears to be one of the most frequently mutated intellectual disability (ID) genes, but that the range of phenotypes caused by ARID1B mutations seems to be extremely wide. Thus, it is one of the most interesting ID genes identified so far in the exome sequencing era. In this article, we review the literature surrounding ARID1B and attempt to delineate the ARID1B phenotype. The vast majority of published ARID1B patients have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 25 publications
6
96
2
Order By: Relevance
“…Other findings, present in a smaller subgroup of CSS patients are determined to have small 5th finger or toe nails, short fifth finger, feeding difficulties, agenesis of the corpus callosum, seizures, myopia, and growth delay in the same study (7).…”
Section: Discussionmentioning
confidence: 66%
“…Other findings, present in a smaller subgroup of CSS patients are determined to have small 5th finger or toe nails, short fifth finger, feeding difficulties, agenesis of the corpus callosum, seizures, myopia, and growth delay in the same study (7).…”
Section: Discussionmentioning
confidence: 66%
“…Phenotypic variability of Coffin-Siris syndrome was recognized prior to identification of its genetic heterogeneity [Schrier Vergano and Deardorff, 2014]. Similarly, significant phenotypic variability has been reported in individuals with intellectual disability due to an ARID1B mutation [Santen et al, 2013[Santen et al, , 2014. Further, phenotypes associated with mutations in ARID1B and multiple other genes encoding components of the BAF complex show significant overlap (Table II) Kosho et al, 2014;Miyake et al, 2014;Bramswig et al, 2015].…”
Section: Discussionmentioning
confidence: 94%
“…2 in Shain et al, 2015]. Recognizing the dual role of the BAF complex in malignancies and intellectual disabilities, the concern for an increased malignancy risk has previously been considered [Santen et al, 2012[Santen et al, , 2014. No increased malignancy risk has been noted in patients with truncating ARID1B mutations, despite such mutations occurring somatically in malignancies [Santen et al, 2012[Santen et al, , 2014.…”
Section: Distinct Syndromes or One Heterogeneous Phenotypic Spectrum?mentioning
confidence: 95%
“…In addition, mutations in ARID1B leading to haploinsufficiency were later identified in CoffinSiris syndrome (CSS), which is characterized by ID, severe speech impairment, coarse facial features, microcephaly, developmental delay, and hypoplastic nails of the fifth digits (MIM 135900) (12)(13)(14). Mutations in other genes within the BAF complex have also been found to cause CSS, but ARID1B mutations account for approximately 70% of cases (15). In 2014, the phenotypic spectrum of CSS was further broadened when an individual with CSS with a de novo frameshift mutation in ARID1B presented with extreme obesity, macrocephaly, hepatomegaly, hyperinsulinism, and polycystic ovarian syndrome (16).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review identified the major features associated with ARID1B haploinsufficiency to be ID, speech delay, coarse facies, and hypertrichosis. Minor features, present in a smaller but significant proportion of individuals, included finger/toe abnormalities, feeding difficulties, agenesis of the corpus callosum, seizures, myopia, and growth delay (15). However, the data were primarily from individuals with a prior clinical diagnosis of CSS and therefore there is likely to be significant ascertainment bias.…”
Section: Discussionmentioning
confidence: 99%